Harry Potter and the sorcerer's stone - Henderson, Duncan; Columbus, Chris; Kloves, Steven; Heyman, David, 1961-; Radcliffe, Daniel, 1989-; Grint, Rupert, 1988-; Watson, Emma, 1990-; Cleese, John.; Coltrane, Robbie; Davis, Warwick; Griffiths, Richard, 1947-; Harris, Richard, 1930-2002.; et al. (Burbank, Calif. : Distributed by Warner Home Video, 2007)
Harry Potter, an orphaned child that has spent the first ten years of his life living under the stairs of his aunt and uncle's house, is invited to join the Hogwarts School of Witchcraft and Wizardry. He learns his destiny lies in the realm of magic and fantasy.
Title from container.
Based on the novel by J.K. Rowling.
Originally released as a motion picture in 2001.
On container spine: Year one.
Director of photography, John Seale ; editor, Richard Francis-Bruce ; music, John Williams ; production designer, Stuart Craig.
Daniel Radcliffe, Rupert Grint, Emma Watson, John Cleese, Robbie Coltrane, Warwick Davis, Richard Griffiths, Richard Harris, Ian Hart, John Hurt, Alan Rickman, Fiona Shaw, Maggie Smith, Julie Walters.
Keywords: Rowling, J. K. -- Film and video adaptations; Potter, Harry (Fictitious character) -- Drama; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Drama; Wizards -- Drama; Magic -- Drama; Friendship -- Drama; Feature films; Fantasy films; Action and adventure films; Children's films; Film adaptations; Films for the hearing impaired; Action and adventure films